Introduction to linear control systems - Bavafa-Toosi, Yazdan (Academic Press, 2017)
'Introduction to Linear Control Systems' is designed as a standard introduction to linear control systems for all those who one way or another deal with control systems. It can be used as a comprehensive up-to-date textbook for a one-semester 3-credit undergraduate course on linear control systems as the first course on this topic at university.